Evaluation of dual-purpose (milk and meat) animals - Syrstad, O.
(Fr, Es)
Ilus., 6 ref.
Keywords: GANADO; RAZAS MIXTAS; PRODUCCION LECHERA; PRODUCTIVIDAD; VALOR NUTRITIVO; VALOR ECONOMICO; VARIACION GENETICA; SISTEMAS DE EXPLOTACION; EVALUACION; ITALIA; REVISTA MUNDIAL DE ZOOTECNIA